Flexible SAW Microfluidic Devices as Wearable pH Sensors Based on ZnO Nanoparticles - Luigi Piro; Leonardo Lamanna; Francesco Guido; Antonio Balena; Massimo Mariello; Francesco Rizzi; Massimo De Vittorio (Nanomaterials, 2021)
In this work, a new flexible and biocompatible microfluidic pH sensor based on surface acoustic waves (SAWs) is presented. The device consists of polyethylene naphthalate (PEN) as a flexible substrate on which aluminum nitride (AlN) has been deposited as a piezoelectric material. The fabrication of suitable interdigitated transducers (IDTs) generates Lamb waves (L-SAW) with a center frequency ≈500 MHz traveling in the active region. A SU-8 microfluidics employing ZnO nanoparticles (NPs) functionalization as a pH-sensitive layer is fabricated between the IDTs, causing a shift in the L-SAW resonance frequency as a function of the change in pH values. The obtained sensitivity of ≈30 kHz/pH from pH 7 to pH 2 demonstrates the high potential of flexible SAW devices to be used in the measurement of pH in fluids and biosensing.